1994
DOI: 10.1073/pnas.91.16.7450
|View full text |Cite
|
Sign up to set email alerts
|

Increase of synaptic density and memory retention by a peptide representing the trophic domain of the amyloid beta/A4 protein precursor.

Abstract: NeurobiologyIncrease of synaptic density and memory retention by a peptide representing the trophic domain of the amyloid ,t/A4 protein precursor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(126 citation statements)
references
References 17 publications
3
120
0
3
Order By: Relevance
“…Indeed, studies on neuronal or non-neuronal cultures have demonstrated that APP s can promote cell growth. In this regard, Roch et al (25) have shown that a peptide containing the neurotrophic domain of APP increases the number of synapses in the cortex of rats during learning in the water maze. Moreover, Huber et al (50) recently have reported that the number of synapses and the level of endogenous APP at synapses in the cerebral cortex are increased in rats bred in an enriched environment, compared with rats bred in standard conditions, again suggesting a role for APP in the formation of new synapses during learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies on neuronal or non-neuronal cultures have demonstrated that APP s can promote cell growth. In this regard, Roch et al (25) have shown that a peptide containing the neurotrophic domain of APP increases the number of synapses in the cortex of rats during learning in the water maze. Moreover, Huber et al (50) recently have reported that the number of synapses and the level of endogenous APP at synapses in the cerebral cortex are increased in rats bred in an enriched environment, compared with rats bred in standard conditions, again suggesting a role for APP in the formation of new synapses during learning.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonspatial͞item recognition memory depends on cortical structures (e.g., visual association areas, perirhinal, entorhinal, and the frontal cortices) rather than the hippocampus per se (24). A peptide derived from APP was shown to increase the number of presynaptic terminals in the frontoparietal cortex of rats at doses improving memory retention in a water maze (25).…”
Section: Discussionmentioning
confidence: 99%
“…These observations provide a mechanistic link between hAPP and excitoprotective effects observed in different in vivo models (5,(25)(26)(27). Our findings also suggest that alterations of hAPP levels or functions by genetic or environmental processes could impair astroglial glutamate/aspartate uptake and thereby result in excitotoxicity and disturbed neurotransmission.…”
Section: Fig 5 Effect Of Recombinant S-happ695 and S-happ751 Onmentioning
confidence: 99%
“…The levels of neuronal hAPP expression directed by the NSE promoter resulted in only moderate elevations of total APP expression above levels found in nontransgenic controls and, hence, were substantially lower than those found in hAPP models that develop Alzheimer's disease-type neuropathology (8,(22)(23)(24). NSE-driven neuronal overexpression of hAPP in transgenic mice or intracerebroventricular infusion of hAPP fragments in nontransgenic rodents increased the number of presynaptic terminals in the neocortex and protected neurons against ischemia and excitotoxins (5,22,(25)(26)(27), suggesting that APP may fulfill important neurotrophic and neuroprotective functions in vivo. In vitro studies suggest that s-APP may prevent excitotoxicity by stabilizing intraneuronal calcium levels (4).…”
mentioning
confidence: 99%
“…A 17 amino acid peptide fragment immediately C-terminal to the KPI domain is probably responsible for the memory enhancing properties of APP and may lead to an increase in the number of presynaptic terminals [138].…”
Section: In Vivo Studies: Appmentioning
confidence: 99%